Analysis of Service Quality on Lestari Seserahan SME Customer Satisfaction with the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) Methods - Fransisca Debora; Nadia Fasa; Hamdani Aris Sudrajat; Astrie Apriliani (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Lestari Seserahan is a business unit engaged in offering services, utilizing business digitalization to promote its business to achieve customer satisfaction. Customer satisfaction can, of course, be influenced by various factors such as the number of manufacturers offering in the same field, the price and quality offered, and the location of available business locations. Based on this, Small and Medium Enterprise (SME) business actors want to know the factors that can influence customer satisfaction so that there are no wrong steps in determining what strategy will be used to make improvements and maintain the level of customer satisfaction using the Customer Satisfaction Index (CSI) method and Importance Performance Analysis (IPA) method. The purpose of the CSI method is to determine customer satisfaction. In contrast, the IPA method aims to identify attributes based on their respective importance and is illustrated using a Cartesian diagram. The calculations using the CSI method yield results of 92.20% and are included in the "Very Satisfied" category, followed by the IPA method, which is described in the Cartesian diagram that no attributes are included in Quadrant I (Top Priority). In Quadrant II (Maintain Achievement), attributes 1, 2, 3, 9, 10, 11, 12, 13, 14, 15, 17, and 19. In Quadrant III (Low Priority), namely attributes 4, 5, 6, 7, 16, and 18. In Quadrant IV (Excessive), only one attribute is included in the plotting of this quadrant, namely attribute 8.